2020
DOI: 10.9734/ajahr/2020/v6i330074
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin-Regulated Physiological Parameters Affected by an Exogenous Dopamine Spray in Brussels Sprout (Brassica oleracea var. gemmifera)

Abstract: Root restriction on the first stage of seedling growth decreases post-transplant biomass accumulation. Several studies in different vegetables and ornamental plants have suggested that this restriction would be overcome by means of a single 6-benzylaminopurine (BAP) spray. Based on this, the aim of this work was to evaluate the effects of both pre-transplant single BAP and dopamine (a cytokinin antagonist) sprays on the growth of Brussels sprout (Brassica oleracea var. gemmifera) plants grown in 200 plug cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…These authors showed that exogenous dopamine increased the content of glucose and fructose by increasing the expression of sucrose phosphate synthase, cell wall invertase and neutral invertase. However, previous data in Brussels sprouts indicated that dopamine spraying did not modify the root:shoot ratios (Miglioli et al, 2020).…”
Section: Tablementioning
confidence: 77%
See 2 more Smart Citations
“…These authors showed that exogenous dopamine increased the content of glucose and fructose by increasing the expression of sucrose phosphate synthase, cell wall invertase and neutral invertase. However, previous data in Brussels sprouts indicated that dopamine spraying did not modify the root:shoot ratios (Miglioli et al, 2020).…”
Section: Tablementioning
confidence: 77%
“…One possibility is to use endogenous inhibitors of cytokinin synthesis such as dopamine (Van Staden et al, 2008). Although there is little information on the effects of the exogenous spraying of plants with dopamine, most studies mention that dopamine works as a stimulant rather than as an inhibitor of metabolism, to compensate for situations of hydric, saline, thermal and nutrient stress (Jiao et al, 2019(Jiao et al, , 2021Gao et al, 2020;Lan, et al, 2020;Liu et al, 2020a, b;Miglioli et al, 2020;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…J.L. Miglioli et al (2020) demonstrated that a decrease in RGR, NAR, an increase in DM of Brassica oleracea var. gemmifera was caused by treatment with 6-benzylaminopurine, while the opposite changes were caused by dopamine.…”
Section: Introductionmentioning
confidence: 99%
“…J.L. Miglioli et al (2020) demonstrated that a decrease in RGR, NAR, an increase in DM of Brassica oleracea var. gemmifera was caused by treatment with 6-benzylaminopurine, while the opposite changes were caused by dopamine.…”
Section: Introductionmentioning
confidence: 99%